Ke arah pewujudan perkhidmatan awam yang bersih, cekap dan amanah - Yeop Abdullah, Othman (Unit Pemodenan Tadbiran Malaysia, 1989)
The Malaysian Public Service plays a multifacated role performs activities geared towards ensuring the right environment, tempo and direction for national development. To perform these activities more effectively there is a need for a clean, efficient and trusworthy service.'Clean' here refers to that of the body, mind and the environment for they contribute towards productivity. 'Efficient' refer to knowledge and skills as well as courtcousness and quality of work. 'Trustworthy' refers to the 'psychological contract' between the government and the individual as regards each other's expectations.Efforts to improve the image and performance of the public service prior to the 80's focused on structural changes, which include the setting up of new agencies, systems and procedural changes, office automation and computerisation and staff development. However, in the 80's several programmes were implemented to inculcate positive attitudes and values among the staff. These include Ethics in the Public Service, the Excellent Office Award, the Inculcation of Islamic Values and the Leadership by Example programmes.